SCOPING STUDY INTO HUMAN RIGHTS-BASED APPROACHES TO EDUCATION IN SOUTHEAST ASIA (Proceedings of International Conference on Special Education, 2017)
The right to education is a universally recognized human right. Like all human rights, it is inalienable, indivisible, interdependent and interrelated with other human rights. As such it is an enabling rights as well because it allows people to exercise and strengthen their voice to claim and secure their rights (Global Campaign for Education, n.d.). But while the right to education is internationally recognized, it remains to be one of the biggest challenges to date, as millions of children are still denied of their basic entitlement to education. SEAMEO INNOTECH, in fulfilling its mandate to provide innovative solution to address the educational needs and concerns of the countries in the region, this study identifies the approaches that each SEAMEO member country has employed in implementing rights-based approach to education. Through a descriptive case study method, this research answered the question, what are the nature and extent of approaches to human rights-based education of the 9 member countries in SEA? This study brings to fore the 9 (i.e. Brunei Darussalam, Cambodia, Indonesia, Lao PDR, Malaysia, Myanmar, Philippines, Thailand and Vietnam) Southeast Asian (SEA) countries’ diverse strategies in implementing rightsbased approach to education using a common framework. Moreover, the different programs and projects of the 9 SEA countries on human rights-based education, effective practices, lessons learned and areas for further strengthening, as well as the barriers for children and citizens to claim their right to education were identified.